Molecular Biomarkers for Diagnosis of Oral Cancer: An Overview - Mojumder, Dipayan; Paul, Satabdi; Podder, Anupam (International Journal of Human and Health Sciences (IJHHS), 2022)
Oral cancer is one of the six leading cancers in the world and is a constant threat to the health sector in developing countries as well as developed ones. Late presentation, due to lack of awareness and invasive incisional biopsy is the crucial factor for this. Nowadays, scientists are trying to find out an easy and reliable method of early diagnosis of oral cancer and molecular biomarkers might be very helpful for that. This review was aimed to evaluate the published literature on molecular biomarkers which are related to oral cancer. For this, advanced searching was applied by specific keywords in PubMed-Medline resource database and found 12466 publications were clinical trials on humans. Then after applying all inclusion criteria, 19 articles were included finally in the review. This paper uncovered that recognition of biomarkers will be useful for the early detection of oral cancer and their prognosis after treatment. We can suggest that p53, EGFR, miR-34a, miR-143 estimation is important to decide the conceivable risk of oral malignant growth advancement in the speculated oral lesion and after the curative procedure EGFR, Podoplanin and miR-21can aid us regarding the prognosis of patient. International Journal of Human and Health Sciences Vol. 06 No. 01 January’22 Page: 11-16